2019
DOI: 10.2116/analsci.19p350
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted Synthesis of N,S-co-carbon Dots as Switch-on Fluorescent Sensor for Rapid and Sensitive Detection of Ascorbic Acid in Processed Fruit Juice

Abstract: To achieve a rapid, sensitive, and economical method for the detection of ascorbic acid (AA) in the presence of Fe 3+ , a nitrogen and sulfur co-doped carbon dots (N,S-co-CDs) based fluorescence sensing system was developed. In this work, N,S-co-CDs were successfully synthesized via a one-step microwave-assisted method within 2.5 min using ammonium citrate and L-cysteine as precursors. The fluorescence of N,S-co-CDs was quenched (off) by Fe 3+ through a static-quenching mechanism. Subsequently, the fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The zeta potential of N, S-CDs was measured to be nearly −17.4 mV, which was attributed to the large number of nitrogen hydrogen bond and carbonyl groups present on the surface of N, S-CDs. However, the zeta-potential dropped to −26.70 mV after adding TAP to the N, S-CDs solutions, showing that the hydroxyl and hydrogen bonds in TAP interact with N, S-CDs to generate complexes such as carboxyl and amine groups, which is further validation of the static quenching results [ 36 ].…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The zeta potential of N, S-CDs was measured to be nearly −17.4 mV, which was attributed to the large number of nitrogen hydrogen bond and carbonyl groups present on the surface of N, S-CDs. However, the zeta-potential dropped to −26.70 mV after adding TAP to the N, S-CDs solutions, showing that the hydroxyl and hydrogen bonds in TAP interact with N, S-CDs to generate complexes such as carboxyl and amine groups, which is further validation of the static quenching results [ 36 ].…”
Section: Resultsmentioning
confidence: 81%
“…According to the Figure 4 a, a typical absorption peaks at 265 nm could be interpreted as the π-π* (C=C or C=O) [ 35 ] and n-π* (C=N or C-OH) electronic transitions. Studies have shown that doping properly could cause the change of local surface state and the recombination of excited-state energy, promoting the strong fluorescence emission of N, S-CDs in the form of main chromophore, which caused these characteristic absorptions to occur [ 31 , 36 ]. It can be found that the fluorescence intensity of N, S-CDs increased initially and then decreased, increasing the excitation wavelength ( Figure 4 b), and when excited at 372 nm, the N, S-CDs reflects the strongest blue fluorescence (inset of Figure 4 a) near the emission peak of 446 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The color of the complex formed between Fe 3+ and phen is pale yellow, which changes to orange-red when the Fe 3+ is reduced to Fe 2+ . This principle was used herein as a probe for the detection of AA since AA can reduce Fe 3+ to Fe 2+ , 41,42 hence changing the color of the complex; the reaction between Fe 3+ -(phen) 3 and AA is given in eqn (1) in Fig. 1S.…”
Section: Deposition Of Probes and Samplementioning
confidence: 99%
“…[5][6][7][8] In addition, the content of Fe 3+ ions in environmental water is an important indicator for monitoring water pollution. [9][10][11][12] Therefore, it is very important to develop sensitive analytical methods for Fe 3+ in biological and environmental samples. Recently, GQDs have been used as an important fluorescence sensor platform for the detection of Fe 3+…”
Section: Introductionmentioning
confidence: 99%